Value of anatomical partitioning of the retroperitoneal space in determining the origin of neurogenic tumors - Yuwei Li; Haowen Zhao; Jingjing Chen; Huacheng Chen; Guangmao Ni; Yanming Ge; Chunjing Liang; Peng Dong (BMC Cancer)
Abstract Background To analyze the anatomical partitioning of the retroperitoneal space and determine the distribution patterns of primary retroperitoneal neurogenic tumors (PRNTs). Methods Retrospectively analyze the clinical data and CT data of 401 patients with single-injection PRNT confirmed by surgical pathology, including 103 cases of neuroendocrine origin, 148 cases of neuroectodermal origin, and 150 cases of peripheral nerve origin. The retroperitoneal space was divided into the anterior pararenal space, posterior pararenal space, perirenal space, and great vessel space. The anatomical location of each PRNT was determined using axial CT images, and distribution patterns of PRNTs with different pathological properties were analyzed. Results There were statistically significant differences in the distribution of benign and malignant PRNTs (p < 0.01), PRNTs from different tissues (p < 0.01), and PRNTs of different pathological types (p < 0.01) in different anatomical divisions. The occurrence of PRNTs varied significantly by age group, with statistically significant differences across pathological types (p < 0.01). Conclusion The anatomical distribution of PRNT could provide an effective imaging basis for the diagnosis and differential diagnosis of PRNT, aiding in more accurate clinical assessment and treatment planning.